Cadherin-7 Regulates Mossy Fiber Connectivity in the Cerebellum - Ken-ichiro Kuwako; Yoshinori Nishimoto; Satoshi Kawase; Hirotaka James Okano; Hideyuki Okano (Cell Reports, 2014)
Summary: To establish highly precise patterns of neural connectivity, developing axons must stop growing at their appropriate destinations and specifically synapse with target cells. However, the molecular mechanisms governing these sequential steps remain poorly understood. Here, we demonstrate that cadherin-7 (Cdh7) plays a dual role in axonal growth termination and specific synapse formation during the development of the cerebellar mossy fiber circuit. Cdh7 is expressed in mossy fiber pontine nucleus (PN) neurons and their target cerebellar granule neurons during synaptogenesis and selectively mediates synapse formation between those neurons. Additionally, Cdh7 presented by mature granule neurons diminishes the growth potential of PN axons. Furthermore, knockdown of Cdh7 in PN neurons in vivo severely impairs the connectivity of PN axons in the developing cerebellum. These findings reveal a mechanism by which a single bifunctional cell-surface receptor orchestrates precise wiring by regulating axonal growth potential and synaptic specificity. : Spatiotemporally orchestrated mechanisms for terminating axonal growth and forming specific synapses are essential in establishing precise neural connectivity. Kuwako et al. demonstrate that cadherin-7 critically regulates the connectivity of the cerebellar mossy fiber circuit by mediating growth inhibition of innervating mossy fiber axons and selective synapse formation between mossy fiber neurons and cerebellar granule neurons. This study reveals that a single cell-surface receptor may play a dual role in axonal growth termination and synaptic specificity to develop precise wiring.